Applications of High-Performance Computing and Cloud Computing in the Course on Distributed Applications Development - Coutinho, Emanuel; Paillard, Gabriel (International Journal of Computer Architecture Education, 2013)
The use of High-Performance Computing in undergraduate courses has become increasingly common as these applications are disseminated in research and development institutes and centers. Cloud Computing has become a widely used paradigm in recent years for various services due to its ease of use based on the pay-per-use model. This article aims to describe their applications together in a module in the undergraduate course Distributed Applications Development. Some practices used in both areas were described, as well as strategies used for their integration. A discussion about the course and future plans are presented at the end of the work.